Comparison of MODIS and AERONET derived aerosol optical depth over the Ganga Basin, India - Tripathi, S. N.; Dey, Sagnik; Chandel, A.; Srivastava, S.; Singh, Ramesh P.; Holben, B. N. (HAL CCSD, 2005)
International audience The Moderate Resolution Imaging Spectroradiometer (MODIS) onboard EOS Terra measures global aerosol optical depth and optical properties since 2000. MODIS aerosol products are freely available and are being used for numerous studies. In this paper, we present a comparison of aerosol optical depth (AOD) retrieved from MODIS with Aerosol Robotic Network (AERONET) data for the year 2004 over Kanpur, an industrial city lying in the Ganga Basin in the northern part of India. AOD retrieved from MODIS (? aMODIS ) at 0.55µm wavelength has been compared with the AERONET derived AOD (? aAERONET ), within an optimum space-time window. Although the correlation between ? aMODIS and ? aAERONET during the post-monsoon and winter seasons (R 2 ~0.71) is almost equal to that during the pre-monsoon and monsoon seasons (R 2 ~0.72), MODIS is found to overestimate AOD during the pre-monsoon and monsoon period (characterized by severe dust loading) and underestimate during the post-monsoon and winter seasons. The absolute difference between ? aMODIS and ? aAERONET is found to be low (0.12±0.11) during the non-dust loading season and much higher (0.4±0.2) during dust-loading seasons. The absolute error in ? aMODIS is found to be about ~25% of the absolute values of ? aMODIS . Our comparison shows the importance of modifying the existing MODIS algorithm during the dust-loading seasons, especially in the Ganga Basin in northern part of India.